Throughcare Service for Elderly Prisoners - Suwannakart, Phatsaporn; Chitsawang, Sumonthip (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2022)
The purpose of this article is to examine the Administration of Criminal Justice issues in elderly prisoners, to study the principle of a Throughcare service, and to propose a guideline on Throughcare service for Elderly prisoners. From the principle of Throughcare service that should provide services to all prisoners, both during and after their sentences. Bringing from this concept, it comes to present an analysis of the four key elements for a successful Throughcare service. The first element is ‘Integrated Case Management’ in which the provider must understand the risk and the specific need of the elderly inmates to ensure that all high risk is supervised effectively after released. The second element is ‘Planning’ that assists prisoners and their families to prepare for release and to resettle in the community. The third element is ‘Coordinated’ which needs the collaboration between all agencies involved in delivering services to prisoners both within the prison and upon release. The fourth element is ‘Services’ which has to develop knowledge of throughcare on the quality of treatment for the elderly prisoners, including the services on housing, health, mental, finance, drug treatment, parent and community involvement.